2020
DOI: 10.2147/cmar.s277291
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prognostic Significance of Inflammatory Biomarkers in Patients with Breast Cancer Skeletal Metastases</p>

Abstract: Purpose: Skeletal metastases are a common problem in breast cancer patients. Identifying new prognostic factors can improve survival estimations and guide healthcare professionals in therapeutic decision-making. Our study aimed to determine the prognostic value of inflammatory biomarkers such as neutrophil-to-lymphocyte ratio (NLR), lymphocyte-tomonocyte ratio (LMR), and C-reactive protein/albumin ratio (CAR) in patients with breast cancer skeletal metastases. Patients and Methods: Clinical data from 212 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…About 20%–30% of breast cancer patients with early age will finally develop metastatic lesions (Early Breast Cancer Trialists' Collaborative G, 2005; Xie et al, 2019). For female patients, plenty of studies had investigated various markers to monitor disease change as to react timely (Huang, Hua, et al, 2020; Wang et al, 2020; Yang et al, 2020). However, there were a few researches about predictive model for metastatic male patients.…”
Section: Discussionmentioning
confidence: 99%
“…About 20%–30% of breast cancer patients with early age will finally develop metastatic lesions (Early Breast Cancer Trialists' Collaborative G, 2005; Xie et al, 2019). For female patients, plenty of studies had investigated various markers to monitor disease change as to react timely (Huang, Hua, et al, 2020; Wang et al, 2020; Yang et al, 2020). However, there were a few researches about predictive model for metastatic male patients.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al (9) reported that an increased preoperative CAR (≥0.029) was an independent risk factor for decreased OS (HR, 9.189; P=0.003) and DFS (HR, 2.225; P=0.024) in patients with non-metastatic BC. By contrast, Wang et al (21) identified that there was no association between elevated CAR (≥0.34) and the survival of BC patients with skeletal metastases in multivariate analysis. There are several explanations for these contradicting results such as differences in the optimal cut-off value for CAR, the selection of study subjects, the timing of the pre-treatment blood samples and the follow-up time.…”
Section: Discussionmentioning
confidence: 90%
“…By contrast, Wang et al. ( 21 ) identified that there was no association between elevated CAR (≥0.34) and the survival of BC patients with skeletal metastases in multivariate analysis. There are several explanations for these contradicting results such as differences in the optimal cut-off value for CAR, the selection of study subjects, the timing of the pre-treatment blood samples and the follow-up time.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“… 19 MLR, the ratio of monocytes and lymphocytes, is also significantly related to poor prognosis of breast cancer patients. 45 Serum albumin, a routine item tested in clinical practice, has been explored as an independent parameter of clinical outcomes in some malignancies, including breast cancer, and a reduction in the albumin level indicates malnutrition, which might lead to a poor prognosis in cancer patients. 24 , 46 The PNI was summed using serum albumin levels and the peripheral lymphocyte counts, which have been proven to reflect the nutritional status of patients and are associated with their survival in many studies.…”
Section: Discussionmentioning
confidence: 99%